An alternative to encourage and create shelters - Alcarazo V., Yober P. (2005)
This is an article that allows us to meditate about the importance that you/they offer us the places and welcome spaces in the families of low economic resources. I believe, for my experience of internal in The House of the Family, when giving them the possibility of "to feed" in a different way, by means of the word, the game, with one listens attentive, respectful and our welcome, the families can overcome their own psychological difficulties.